New Insight into the Substrate Selectivity of Bovine Milk γ-glutamyl Transferase via Structural and Molecular Dynamics Predictions - Lichuang Cao; Cameron J. Hunt; Anne S. Meyer; René Lametsch (Molecules, 2023)
Bovine milk γ-glutamyltransferase (BoGGT) can produce γ-glutamyl peptides using L-glutamine as a donor substrate, and the transpeptidase activity is highly dependent on both γ-glutamyl donors and acceptors. To explore the molecular mechanism behind the donor and acceptor substrate preferences for BoGGT, molecular docking and molecular dynamic simulations were performed with L-glutamine and L-γ-glutamyl-p-nitroanilide (γ-GpNA) as donors. Ser450 is a crucial residue for the interactions between BoGGT and donors. BoGGT forms more hydrogen bonds with L-glutamine than γ-GpNA, promoting the binding affinity between BoGGT and L-glutamine. Gly379, Ile399, and Asn400 are crucial residues for the interactions between the BoGGT intermediate and acceptors. The BoGGT intermediate forms more hydrogen bonds with Val-Gly than L-methionine and L-leucine, which can promote the transfer of the γ-glutamyl group from the intermediate to Val-Gly. This study reveals the critical residues responsible for the interactions of donors and acceptors with the BoGGT and provides a new understanding of the substrate selectivity and catalytic mechanism of GGT.